Classificação dedistribuições holomorfas em variedades de Hopf - Antônio Marcos Ferreira da Silva (2014)
In this thesis, we classify nonsingular holomorphic foliations of dimension and codimension one on classical, generic and intermediate Hopf manifolds of dimension n .= 3. We also did a study of singular set of singular holomorphic distributions in arbitrary Hopf manifolds.Finally, we demonstrated that is true a version of the Brunella's Conjecture for codimension one foliations on classical Hopf manifolds is true.